Post‐transplant immune complex nephritis in a patient with systemic lupus erythematosus associated with ANCA vasculitis. (29th January 2017) - Sanchez, Carlos; Rebolledo, Alejandra; Gahona, Junior; Rojas, Mauricio; Jiménez, Raquel; Bojórquez, Aurora
Abstract: Nearly 20% of SLE corresponds to the pediatric population, and 75% of them have kidney involvement representing an important etiology of chronic kidney disease. A correlation between SLE and ANCA‐associated vasculitis has been identified as an overlapping syndrome. Kidney allograft recurrence is rare in SLE when disease control is achieved and with nowadays immunosuppression treatment. Histologic transformation is unusual, especially when there are negative serologic markers and no immune complex deposition reported in native kidneys. A 17‐year‐old female with crescentic glomerulonephritis, p‐ANCA‐positive antibodies with pauci‐immune pattern in kidney biopsy develops end‐stage renal disease requiring hemodialysis. Deceased donor kidney transplant was performed receiving triple immunosuppression thereafter. Thirteen months later serum creatinine rises without evidence of infection, urinary obstruction, or clinical and serologic disease relapse. Allograft biopsy reports mesangial proliferation and "full‐house" immunofluorescence. The role of ANCA in SLE physiopathology is controversial, and its relation with lupus nephritis is also discordant. ANCA could represent an important factor in the heterogeneity of systemic lupus erythematosus and lupus nephritis.